2004
DOI: 10.1093/ndt/gfh185
|View full text |Cite
|
Sign up to set email alerts
|

On the relative safety of parenteral iron formulations

Abstract: Parenteral iron-related ADEs are rare. Using observational data, overall and most specific ADE rates were significantly higher among recipients of higher molecular weight iron dextran and sodium ferric gluconate complex than among recipients of lower molecular weight iron dextran. These data may help to guide clinical practice, as head-to-head clinical trials comparing different formulations of intravenous iron have not been conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 16 publications
2
105
3
5
Order By: Relevance
“…98 A number of studies document that anaphylaxis, the serious adverse event associated with iron dextran, is largely due to the two high molecular weight products, Imferon, which is no longer available, and Dexferrum, which is not recommended. 40,42,48,49,53,[99][100][101][102][103][104][105][106] Iron sucrose has the least reported adverse events and high molecular weight iron dextran has the highest number of reported adverse events. Low molecular weight iron dextran and ferric gluconate fall in between these two for the number of adverse drug events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…98 A number of studies document that anaphylaxis, the serious adverse event associated with iron dextran, is largely due to the two high molecular weight products, Imferon, which is no longer available, and Dexferrum, which is not recommended. 40,42,48,49,53,[99][100][101][102][103][104][105][106] Iron sucrose has the least reported adverse events and high molecular weight iron dextran has the highest number of reported adverse events. Low molecular weight iron dextran and ferric gluconate fall in between these two for the number of adverse drug events.…”
Section: Resultsmentioning
confidence: 99%
“…Low molecular weight iron dextran and ferric gluconate fall in between these two for the number of adverse drug events. 40,46,48,56,60,98 Anaphylactic reactions have predominantly been reported with the use of iron dextran. 50,51 Comparisons of the iron sucrose or iron gluconate to low molecular weight iron dextran show no difference in toxicity or efficacy but considerable savings and ease of administration with low molecular weight iron dextran.…”
Section: Resultsmentioning
confidence: 99%
“…At least two studies [2,3] have implicated the higher molecular weight iron dextran, Dexferrum, with substantially higher incidence of anaphylactic-type reactions than the lower molecular weight iron dextran, INFeD, and an editorial [4] requested that FDA remove Dexferrum from the market. However, these studies used as evidence voluntarily submitted reports of adverse drug events entered in the FDA's database.…”
Section: Discussionmentioning
confidence: 99%
“…At least two studies [2,3] have implicated the higher molecular weight iron dextran, Dexferrum, with substantially higher frequencies of life-threatening adverse drug events including anaphylactic-type reactions than the lower molecular weight iron dextran, INFeD. An editorial published in 2008 [4] stated, ''We urgently recommend avoiding use of HMW iron dextran in all clinical practice settings.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated data show that lowmolecular weight iron dextran does not share this higher risk. Studies ranging from dialysis database reviews to a European Medical Agency review have shown no difference in risk with low-molecular weight iron dextran versus other iron products [3][4][5].Recently, this notion of equivalent risk was challenged by a study from the FDA which purported to show a significantly higher rate of "anaphylaxis" with iron dextran compared to other iron products [6]. This study examined 688,183 non-dialysis new users of intravenous iron over 10 years in the outpatient Medicare claims database.…”
mentioning
confidence: 99%